2011
DOI: 10.1088/0031-9155/56/17/016
|View full text |Cite
|
Sign up to set email alerts
|

Improved tumour response prediction with equivalent uniform dose in pre-clinical study using direct intratumoural infusion of liposome-encapsulated186Re radionuclides

Abstract: Crucial to all cancer therapy modalities, is a strong correlation between treatment and effect. Predictability of therapy success/failure allows for the optimization of treatment protocol and aids in the decision of whether additional treatment is necessary to prevent tumour progression. This work evaluated the relationship between cancer treatment and effect for intratumoural infusions of liposome-encapsulated 186 Re to head and neck squamous cell carcinoma xenografts of nude rats. Absorbed dose calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In a radionuclide therapy model, Hrycushko et al. found that taking into account intratumoural heterogeneity for absorbed-dose calculations after local delivery of 186 Re-labelled liposomes provided better correlation with tumour shrinkage than using the average tumour absorbed dose [303]. While such precise intratumoural distribution analysis is non-trivial, it is expected that future technological improvements will simplify this type of analysis, and will allow to correlate for example the spatial distribution of a radiolabelled drug with the therapeutic outcome with better accuracy than simply using the total amount of drug delivered to the tumour.…”
Section: Applications Of Radiolabelled Liposomesmentioning
confidence: 99%
“…In a radionuclide therapy model, Hrycushko et al. found that taking into account intratumoural heterogeneity for absorbed-dose calculations after local delivery of 186 Re-labelled liposomes provided better correlation with tumour shrinkage than using the average tumour absorbed dose [303]. While such precise intratumoural distribution analysis is non-trivial, it is expected that future technological improvements will simplify this type of analysis, and will allow to correlate for example the spatial distribution of a radiolabelled drug with the therapeutic outcome with better accuracy than simply using the total amount of drug delivered to the tumour.…”
Section: Applications Of Radiolabelled Liposomesmentioning
confidence: 99%
“…Conversely, the MRI contour for Patient 5 indicated slightly less dose homogeneity than the PET-based contours because the MRI DVH had a larger low dose shoulder. Accurate qualification of the tumor dose homogeneity is important because non-uniform dose distributions in TRT can have significant clinical implications for the treatment response and toxicity (O’Donoghue, 1999, Amro et al, 2010, Hanaoka et al, 2014, Hrycushko et al, 2011). Specifically, one study by Hrycushko et al (2011), investigating the impact of 186 Re-liposome dose heterogeneity in head and neck squamous cell carcinoma mouse xenografts, found that cold spots resulted in reduced tumor control (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate qualification of the tumor dose homogeneity is important because non-uniform dose distributions in TRT can have significant clinical implications for the treatment response and toxicity (O’Donoghue, 1999, Amro et al, 2010, Hanaoka et al, 2014, Hrycushko et al, 2011). Specifically, one study by Hrycushko et al (2011), investigating the impact of 186 Re-liposome dose heterogeneity in head and neck squamous cell carcinoma mouse xenografts, found that cold spots resulted in reduced tumor control (i.e. tumor shrinkage) analogous to the results seen for human patients undergoing external beam radiotherapy (Niemierko and Goitein, 1991, Tomé and Fowler, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Based on biodistribution results in rats, dose distributions were modeled and radiobiological indexes determined, following direct injection of 188 Re-liposomes into the lumpectomy cavity (215, 216). The same group also carried out a similar work with head and neck squamous cell carcinoma, following direct intratumoral infusion of 99m Tc-labeled liposomes (217, 218). These theoretical results would need to be confirmed in vivo .…”
Section: Re Particulatesmentioning
confidence: 99%